An observation on the quality of interfaces in order to understand the complexity and coherence of informal settlement: A study on Tamansari Kampung in Bandung. (May 2018) - Sawira, S; Rahman, T
Abstract: Self-organized settlements are formed within the limited capacity of the inhabitants with or without the Government's interventions. This pattern is mostly found in the informal settlements, where occupants are the planners who are guided by their needs, limited resources and vernacular knowledge about place making. Understanding the process of its development and transformation could be a way of unfolding the complexity it offers to a formal urban setting. To identify the patterns of adaptation process, a study of morphological elements (i.e. house form, streets) could be a possible way. A case study of an informal settlement (Kampung of Tamansari, Bandung in Indonesia) has been taken to dissect these elements. Two of important components of the study area: house forms and streets created the first layer of urban fabric. High population density demanded layers of needs and activities which eventually guided the multifunctional characteristics of streets and house forms. Thus, streets create dialogue with the complex built forms-often known as interface is the key element to understand the underneath order of Tamansari. Here interface can be divided into two categories depending on their scale – small and large. Small scale interfaces are comprised of small elements such as, extended platform, fence, steps, low height wall, blank wall and elements to set above, set forth, set over in house forms. These components help to create and define semipublic spaces in the settlement. These spaces could be visually and physically interactive or no interactive which result into active or inactive spaces respectively. Small scale interfaces are common features of the settlement, whereas large scale interfaces are placed at strategic locations and act as active spaces. Connecting bridges, open spaces and contours often create special dialogue within and beyond the study area. Interfaces cater diversity in the settlement by creating hierarchy of spaces. Sense of belonging and scope of personalization of the inhabitants are integral parts of alleyways and thus they create a complex yet coherent urban fabric. Apart from the physical elements, the settlement embodies some intangible assets like social bonding, trust, kinship, empathy and sense of belonging that add value to the spatial quality which is a distinctive character of Tamansari kampung. Informal settlements are certainly complex in nature, as it is an outcome of multiple people working to accommodate multidimensional needs. Whereas in a formal system, approach to cater for need is guided by a set of rules developed by a set of professionals end up in creating prototypes irrespective of necessity, affordability and cultural diversity. Cities throughout the world, are experiencing rapid urbanization creating different urban issues. Therefore, it is highly necessary to address different need and affordability of users and come up with suitable urban solutions. Understanding Tamansari Kampung as an informal settlement will enrich the knowledge and expertise to work in complex urban settings.